PENGARUH GOOD CORPORATE GOVERNANCE (GCG) TERHADAP NILAI PERUSAHAAN PADA PERUSAHAAN MANUFAKTUR YANG TERDAFTAR DI BURSA EFEK INDONESIA TAHUN 2015-2017 - Sutrisno . Sutrisno; Ariyani Indriastuti (Sekolah Tinggi Ilmu Ekonomi Semarang, 2019)
All information in a company's financial statements is useful for investors and users of financial statements because the information contained in financial statements can be used by interested parties or users of financial statements for consideration in making economic decisions, but sometimes the attention of financial statement users or investors is only focused on earnings information. The purpose of this research is to find out. Effect of Good Corporate Governance managerial ownership of institutional ownership and the Audit Committee on Company Value in manufacturing companies listed on the Indonesia Stock Exchange 2015-2017. The population in this study are manufacturing companies listed on the Indonesia Stock Exchange (IDX) in 2015-2017. The companies that became the population in this study were 24 manufacturing companies. The variables in this study were managerial ownership, institutional ownership and an audit committee on Company Value. Methods of data analysis using multiple linear regression, coefficient of determination and hypothesis testing. The results of this study indicate that the managerial ownership regression coefficient is 0.304, t count (3.847)> t table (1.66) and sign (0.000), <(0.05), institutional ownership is 0.337, t count (3.375)> t table (1.66) and sign (0.001) <(0.05) and audit committee 0.341, t count (4.110)>ttable (1.66) and sign (0.000) <(0.05) based on the coefficient test results R2 determination of 62.8%. This means managerial ownership of institutional ownership and audition committee. Together - they have a positive and significant effect on Company Value. This can be proven in the F test of 38,231 in manufacturing companies listed on the Indonesia Stock Exchange 2015-2017. Company value calculation using PBV (price book value) proxy. However, the calculation of company value can be done using other methods such as Tobin's Q because the calculation of company value does not only use PBV. Given the results of this study indicate that a positive effect on a corporate value of good corporate governance